Analysis of OLSR Routing Protocol Performance Based on Gauss-Markov Mobility and Random Walk in Mobile Ad-Hoc Network (MANET) - Heru Nurwarsito; Ervani Sofyana Putra (Journal of Information Technology and Computer Science, 2022)
MANET is included in the network without infrastructure from a collection of nodes that are interconnected to communicate. Routing protocol performance is a measure of the performance of how the ability of the routing protocol works. A routing protocol is needed where the routing table information must be kept up to date at regular intervals such as Optimized Link State Routing (OLSR). MANET is dynamic, so node mobility increases the risk of node failure. Gauss-Markov and random walk are mobility that has a significant impact on the performance of the routing protocol. This study analyzes the effect of mobility on the OLSR protocol in MANET topology using Network Simulator 3.25 with packet delivery ratio (PDR) parameters, end to end delay and routing overhead. The test scenario is done by varying the number of nodes as many as 20, 40, 60, and 80 nodes as well as the minimum and maximum speed of nodes 0-5 m/s, 5-10 m / s, 10-15 m/s, and 15-20 m/s. PDR results show the highest value on Gauss-Markov with 80 nodes and a minimum and maximum speed of 10-15 m/s of 69.36%. The best end to end delay results is seen in Gauss-Markov with 20 nodes and a minimum and maximum speed of 15-20 m/s of 10.22 ms. The routing overhead results display the best value on a random walk with 20 nodes and a minimum and maximum speed of 0-5 m/s of 8100 packets.